2020
DOI: 10.3390/metabo10120491
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolite Biomarkers for Predicting Residual Feed Intake (RFI) of Young Angus Bulls

Abstract: Residual feed intake (RFI) is a feed efficiency measure commonly used in the livestock industry to identify animals that efficiently/inefficiently convert feed into meat or body mass. Selection for low-residual feed intake (LRFI), or feed efficient animals, is gaining popularity among beef producers due to the fact that LRFI cattle eat less and produce less methane per unit weight gain. RFI is a difficult and time-consuming measure to perform, and therefore a simple blood test that could distinguish high-RFI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…In this particularly low N environment, undernutrition is the major issue, especially during the dry winter season [5]. Animals that efficiently convert feed into meat or body mass have a high difference between their actual feed intake and the expected feed requirements for maintenance and growth (low residual feed intake, RFI) over a particular time period [8]. A recent study demonstrated that feeding cattle with an N-supplemented diet in this environment enhanced rumen fermentation and increased bacterial populations involved in pectin and hemicellulose degradation and ammonia assimilation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this particularly low N environment, undernutrition is the major issue, especially during the dry winter season [5]. Animals that efficiently convert feed into meat or body mass have a high difference between their actual feed intake and the expected feed requirements for maintenance and growth (low residual feed intake, RFI) over a particular time period [8]. A recent study demonstrated that feeding cattle with an N-supplemented diet in this environment enhanced rumen fermentation and increased bacterial populations involved in pectin and hemicellulose degradation and ammonia assimilation [5].…”
Section: Introductionmentioning
confidence: 99%
“…This change in the rumen microbiota structure induced a lower RFI with an increase in the daily LW gain, rumen NH 3 -N, butyrate, and the acetic to propionic acid ratio [5]. High quality feeds have been shown to increase plasma urea which serves as a promising and inexpensive metabolite to predict and categorize bovine RFI values [8,9]. Additionally, dietary proteins in roughages and N utilization are fundamental to growth and development in ruminants, but an estimated 70% of ingested N is excreted as urinary and fecal N which can limit animal productive performance and cause environmental pollution [3].…”
Section: Introductionmentioning
confidence: 99%
“…The advanced analytical chemistry techniques were used to comprehensively measure large numbers of small molecule metabolites in cells, tissues and bio uids, named metabolomics 3 . The blood metabolomics study was largely used to explain or identify the economic traits of livestock [4][5][6] . For a part of milk metabolites were from blood and the blood metabolites could regulate the biological function of mammary cells, the serum metabolomics would be one of useful strategy to explain the mechanism of milk composition differences between different species [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been used to predict RFI ( Kelly et al, 2010 ; Fitzsimons et al, 2013 ; Karisa et al, 2014 ; Foroutan et al, 2020a ), and to explore the molecular physiological or biochemical underpinnings of lean tissue or muscle content in livestock. For example, Lawrence et al (2011) reported a positive correlation between muscularity and concentration of creatinine in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Other metabolites associated with energy and lipid metabolism such as glucose (associated with insulin resistance and energy metabolism), carnitine (associated with glucose, lipid and energy metabolism), and beta-hydroxybutyrate (product of tissue fatty acid catabolism) have been found to be higher in the plasma of HRFI vs. LRFI beef cattle ( Kelly et al, 2010 ; Fitzsimons et al, 2013 ; Karisa et al, 2014 ). Recently, Foroutan and coworkers used three metabolomics platforms including NMR, ICP-MS, and LC-MS/MS to compare a wide range of metabolites in the serum of young, divergent RFI Angus bulls ( Foroutan et al, 2020a ). They found two sets of predictive RFI biomarkers; one included formate (associated with energy metabolism and immune response) and leucine (associated with protein and energy metabolism as well as immune response) (best for NMR), and another set included butyrylcarnitine (associated with energy metabolism and immune response) and LysoPC28:0 (associated with lipid metabolism and immune response) (best for LC-MS/MS), both with high sensitivity and specificity (Area Under the Receiver Operating Characteristic Curve or AUROC >0.85), for distinguishing HRFI from LRFI animals.…”
Section: Introductionmentioning
confidence: 99%